Impact of proposed home based exercise program on non-specific lower back pain intensity and on weight regulation in college females in crises environment (Damascus University Journal of educational and Psychologyical sciences, 2025)
Current study aimed to discern the effect of suggested exercise program on the level of pain intensity and on weight regulation among university female students who suffer from chronic nonspecific lower back pain in the Syrian university environment during the crises. The sample was limited to the colleges of Damascus University and its branches, and the number of the study sample was (89) female who were chosen randomly, and from the age of 17-29 years. The researcher used an adopted exercise program that includes strengthening and stretching exercises, as well as exercises to promote the level of aerobic capacity. In addition, the Numerical Pain Rating Scale (NRS) was applied and the students were classified according to their BMI value. The percentage of normal weight was 42.70% and overweight was 37.08% and obese female students was 20.22% and that the level of pain intensity of the students with normal weight was moderate (2.84), while among the overweight girls was medium (4.63), and among those belonging to the obese category, touched the level of strong pain (5.52). The exercise program had a significant effect (p=0.0001) in reducing both weight and pain intensity. University females tend to be overweight within the course of ongoing crises. The relationship between pain intensity with BMI was statistically significant. Effects of the suggested exercise program were significantly positive in decreasing pain and reducing weight.
Keywords: College Females; Exercise Program; BMI; Pain Intensity